Biomarkers of aggressiveness in genitourinary tumors with emphasis on kidney, bladder, and prostate cancer. (3rd July 2018) - Cimadamore, Alessia; Gasparrini, Silvia; Santoni, Matteo; Cheng, Liang; Lopez-Beltran, Antonio; Battelli, Nicola; Massari, Francesco; Giunchi, Francesca; Fiorentino, Michelangelo; Scarpelli, Marina; Montironi, Rodolfo
ABSTRACT: Introduction : Over the last decade, the improvement in molecular techniques and the acquisition of genomic information has transformed and increased the quality of patient care and our knowledge of diseases. Areas covered : Protein expression levels in immunohistochemistry and molecular biomarkers are reported for their ability to predict recurrence, progression, development of metastases, or patient survival. In particular, for renal cell carcinoma, we take into consideration the biomarkers applicable to immunohistochemistry and with molecular and genetic analyses. In urothelial carcinoma, there is great interest in the possibility of distinguishing the basal vs. luminal subtypes and to acquire deeper insight into the tumor biology through examining exosomes in urine and biomarkers in the serum. In prostate cancer, single gene expression and multiple gene expression classifiers are reviewed as a tool to distinguish indolent vs. aggressive disease. Expert commentary : The genomic information along with the application of ancillary techniques allow the definition of a neoplasia not only by its morphology but also by its biological signature. This continuous increase in knowledge will result in a better comprehension of oncogenesis, development of targeted therapies and optimizing decision-making processes related to patient care